Comparison of Adsorption Conformation of Comb‐Shaped Polycarboxylate on Tricalcium Aluminate (100) and Ettringite (100) Surfaces: A Molecular Dynamics Study. Issue 6 (30th April 2021) - Zhao, Hongxia; Yang, Yong; Shu, Xin; Wang, Tao; Ran, Qianping
Abstract: The adsorption conformations of three comb‐shaped polycarboxylate (PCE) with different numbers of grafted side‐chains on the tricalcium aluminate (C3A) and ettringite surface is studied by all‐atom molecular dynamics (MD) simulations with INTERFACE‐PCFF forcefield. The similarity of absorbed PCEs on both surfaces is backbones of PCEs absorbed on the surface and the side‐chains extended to liquid phase. The difference is that side‐chains of PCEs keep a tilt angle with the C3A crystal but maintain parallel and closer to ettringite crystals. The absolute value of adsorption energy of PCEs on C3A surface is greater than that on ettringite surface, which indicate the stronger interaction between PCEs and C3A than ettringite. PCE with less side chains is favorable for the adsorption due to stronger electrostatic interaction with surface. Adsorption capacity and water‐reducing ability of PCEs are contradictory. Density of water near the solid–liquid interface is more severely decreased by PCE with more side chains. Correlation of the adsorption conformation of PCEs with the flow behaviors of fresh cement paste is summarized. Abstract : The adsorption conformations of three comb‐shaped polycarboxylates (PCEs) on the tricalcium aluminate and ettringite surface is studied by all‐atom molecular dynamics simulations. A comparison of adsorption conformations of PCEs on the two mineral surfaces is taken and correlation of the adsorption conformations of PCEs with the flow behaviors of fresh cement paste is summarized.